Evaluation of the relationship between left atrial strain and exercise tolerance in patients with hypertrophic cardiomyopathy by treadmill stress echocardiography - Su, Ye; Li, Chunmei; Yin, Lixue (Frontiers in Cardiovascular Medicine, 2023)
Objective The aim of this study is to evaluate the left atrial strain (LAS) in patients with hypertrophic cardiomyopathy (HCM) by treadmill exercise stress echocardiography, combined with three-dimensional speckle tracking technology, for predicting exercise tolerance. Methods A total of 97 patients with HCM who underwent treadmill exercise stress echocardiography were recruited in Sichuan Provincial People's Hospital between January 2018 and January 2021, and 30 control subjects were selected to be included in the normal group. HCM patients with their metabolic equivalents (METS) ≤ 6.0 were included in the HCM-1 group, while those with METS > 6.0 were included in the HCM-2 group. The LAS and exercise tolerance were analyzed. The ultrasound parameters that could predict a decrease in exercise tolerance were screened, and a predictive model was constructed. Results It was found that METS, Rest-LASr, Rest-LAScd, and Rest-LASct were significantly lower in HCM patients than those in normal controls. There was a significant difference in age, Target_HR, LVMI, LAVI, E/e'-Rest, E/e'-Peak, Rest-LASr, Rest-LAScd, and Rest-LASct between the HCM-1 and the HCM-2 groups. LASr is an independent resting echocardiographic predictor of METS ≤ 6.0. LASr remained significant for predicting different subtypes (AHCM, asymmetric HCM, and obstructive HCM). Rest-LASr (AUC 0.990) was better at predicting METS ≤ 6.0 than Peak-E/e' (AUC 0.753). A multivariate model (LASr + Age + Target_HR) was established for METS prediction. Conclusion Left atrial reservoir strain (LASr) has the strongest association with METS ≤ 6.0. The LASr is an independent resting predictor of METS ≤ 6.0 and has a good performance record in predicting different subtypes of HCM. Compared with the traditional parameters, Peak-E/e' and Rest-E/e', Rest-LASr is the best predictor. Rest-LASr can serve as a reliable method for HCM patients who are unable to undergo exercise testing but require an urgent evaluation of their METS, which provides a basis for clinical treatment decision-making and treatment effect evaluation.